Psalm 72 in light of the psychological theories of poverty - Mtshiselwa, Ndikho (Verbum et Ecclesia, 2024)
Prior to the 1980s, various theories of poverty have been proposed by psychologists, ranging from, but not limited to, ‘naturalizing perspective’, ‘constitutionally inferior perspective’, or ‘nativist perspective’; to the ‘McClelland approach’ (McClelland 1961 , 1965 , 1973 ); to the ‘attribution theory’; and to Lewis’ ( 1975 ) culture of poverty theory. The theories tease out issues of the accumulated environmental deficits and psychiatric disorders, such as depression as well as the lack of ambition and mental drive to achieve success. However, from the 1980s, psychologists returned to the Lewis’ culture of poverty theory. The World Bank Development Report for 2000–2001’s expansion of Sen’s ( 1999 ) theory, which placed emphasis and/as three-pillars on ‘security’, ‘empowerment’ and ‘opportunity’ led for one, among other psychological bodies, the American Psychological Association to consider various conceptualisation of the theories of poverty. The paper tests the psychological theories of poverty against the background of the historical-literary read poetic text of Psalm 72. Does a poetic reading of Psalm 72 bear a psychological meaning when read within the framework of psychological theories of poverty? Firstly, the paper investigates psychological theories of poverty prior to 1980s to the present. Secondly, in a poetically and historically read Psalm 72, the psychological presuppositions are teased out. In the end, the paper submits with caution that when read within the framework of psychological theories of poverty, the poetically read Psalm 72 produces psychological meaning, which contributes value to the reading of Biblical poetic texts. Intradisciplinary and/or interdisciplinary implications: The article draws on the discipline of psychology, employing the psychology theories of poverty to read an Old Testament poetic text of Psalm 72. The meaning of Psalm 72 is derived from the psychological reading of the historical-literary critically analysed poetic Hebrew Bible text.
free